Estabilidade dinâmica para sistemas quânticos dependentes do tempo - Simsen, Mariza Stefanello (2006)
We study if a time-dependent system is either dynamically stable or unstable, i.e., if the expected value of a positive and discrete observable is a bounded function of time or not. Initially we consider topological properties of the orbits of the states of the system and how these properties are related to dynamical stability. In the case of periodic time dependence, we present a formula that allows one to decide about stability from the behavior of the matrix elements of the resolvent associated with the Floquet operator. Finally, we give an example of Floquet operator with purely point spectrum and exponentially decaying eigenfunctions and dynamical instability.